Nanofiber membrane for detecting Cr < 3 + > as well as preparation method and application of nanofiber membrane

Using 1,4-DHAQ/Cu@GEL-PCL nanofiber membrane as a solid-state fluorescence sensor, nanofiber membranes were prepared using electrospinning technology, and combined with the replacement reaction of 1,4-DHAQ derivatives of Cu2+ and Cr3+, the existing solutions were solved. The technology of detecting chromium ions in industrial wastewater is expensive, time-consuming and complex in operation, achieving rapid detection of high sensitivity and high stability, suitable for rapid analysis of large batches of samples.

CN119162736APending Publication Date: 2024-12-20QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411218422.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing heavy metal ion concentration detection methods have problems such as high cost, long time and complex operation when detecting chromium ions in industrial wastewater, and the linear detection range of existing solid-state fluorescence sensors is not sufficient to meet the needs of industrial wastewater treatment.

Method used

Using 1,4-DHAQ/Cu@GEL-PCL nanofiber membrane as solid-state fluorescence sensor, nanofiber membranes were prepared by electrospinning technology, combining the replacement reaction between 1,4-DHAQ derivatives of Cu2+ and Cr3+ to achieve the fluorescence intensity. It is enhanced to detect Cr3+ ions in water, which is simple to operate and convenient to carry, and is suitable for rapid detection of large batches of samples to be tested.

Benefits of technology

It realizes rapid detection of high sensitivity and high stability of Cr3+ ions in wastewater, simple preparation process, green and environmentally friendly raw materials, suitable for rapid qualitative and quantitative analysis of industrial wastewater, accurate detection results, and suitable for rapid detection and analysis of large batches of samples.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119162736A_ABST
    Figure CN119162736A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of material chemistry and sewage detection, and provides a nanofiber membrane for detecting Cr < 3 + > and a preparation method and application thereof. The preparation method of the nanofiber membrane comprises the following steps: dissolving gelatin and polycaprolactone in a mixed solvent of formic acid and acetic acid, then adding 1, 4-dihydroxy anthraquinone and copper nitrate hexahydrate, and carrying out electrostatic spinning to obtain the nanofiber membrane. The nanofiber can be used for preparing a solid fluorescence sensor for detecting Cr < 3 + > in a solution. The sensor is high in sensitivity and good in stability; the incubation time is short, and the method is suitable for rapid detection and analysis of large-batch to-be-detected samples; the nanofiber membrane is prepared in one step, the preparation process is simple, and the raw materials are green, environment-friendly, economical and easy to obtain; the nanofiber membrane provided by the invention can be stored for at least six months at normal temperature under a dark condition; the fluorescence sensor provided by the invention is a solid sensor, and is simple to operate and convenient to carry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material chemistry and sewage detection, and specifically relates to a method for detecting Cr 3+ Nanofiber membranes and their applications. Background Art

[0002] The disclosure of this background information is intended to enhance understanding of the general background of the invention and should not necessarily be taken as an acknowledgment or any form of suggestion that this information constitutes the prior art already known to a person skilled in the art.

[0003] The booming development of modern industry also produces a large amount of industrial wastewater, which often contains Cr. 3+ , Pb 2+ , Cu 2 + 、Co 2+ Heavy metal ions such as Cr are extremely harmful to human health and the environment. 3+ It is an essential trace element for the human body. Intake of an appropriate amount of chromium can promote human metabolism and sugar absorption. Excessive intake may cause chromium poisoning, damage the skin and respiratory system, and cause a series of skin problems and respiratory diseases. 3+ Can be used with Cr in certain situations 6+ Interconversion, Cr 6+ It has strong carcinogenicity, teratogenicity and neurotoxicity. Therefore, it is necessary to 3 + Cr 6+ Real-time and efficient detection. Existing heavy metal ion concentration detection methods include atomic absorption spectroscopy (AAS), inductively coupled plasma mass spectrometry (ICP-MS), X-ray fluorescence spectroscopy (XRF), high performance liquid chromatography (HPLC) and other methods. Although these methods are very complete and can obtain reliable results, they all require complex pretreatment and the use of large instruments for detection. There are shortcomings such as high detection costs, long detection time, and complex operations, which are difficult to meet the low-cost and high-efficiency detection needs of enterprises.

[0004] Fluorescence sensor technology uses the interaction between the fluorescent detector carried on the sensor and the target ions in the measured solution to perform detection. The larger the specific surface area (S / M) of the fluorescent sensor, the stronger the interaction between the fluorescent detector exposed in the solution and the target ions, and the higher the sensitivity of the fluorescent sensor. Fluorescence sensors can provide real-time monitoring and instant results, which are crucial for timely decision-making in industrial processes. In addition, the development of solid-state fluorescent sensors has improved their portability and ease of use. Among them, electrospinning technology provides significant advantages for the production of nanofibers as substrates for fluorescent sensors, enhancing the interaction between fluorescent detectors and target ions, thereby improving the sensitivity and detection limit of the sensor. In addition, the porosity of electrospun nanofibers facilitates effective mass transfer, thereby achieving rapid response when detecting ions in aqueous solutions.

[0005] Wang Meiling et al. (2011) proposed a substrate made of cellulose acetate by electrospinning for the preparation of a solid-state fluorescent sensor for detecting chromium ions. However, its linear detection range was only 2.5× 10 -9 to 2.5× 10 -8 M. The chromium ion content in most industrial wastewater discharge standards is generally 10 -5 -10 -6 M order of magnitude, it is not suitable for detecting chromium ions in industrial wastewater treatment. Therefore, it is necessary to develop a method with simple operation, accurate detection results and high sensitivity to achieve rapid qualitative and quantitative detection and analysis of heavy metal ions in wastewater solutions. Summary of the invention

[0006] In view of the current lack of solid sensors for detecting chromium ions in wastewater, the present invention provides a method for detecting Cr 3+ The nanofibers can realize rapid detection of trivalent chromium ions in wastewater with high sensitivity and high stability.

[0007] Another object of the present invention is to provide a method for preparing the above-mentioned nanofibers, which can be completed in just one step, with green and environmentally friendly raw materials, economical and easily available, and a simple processing process.

[0008] Another object of the present invention is to provide a method for detecting trivalent chromium ions in wastewater using the above-mentioned nanofibers, which is simple to operate, convenient to carry, has a short detection process, and is suitable for rapid detection and analysis of large quantities of samples to be tested.

[0009] To achieve the above purpose, the present invention adopts the following technical solution.

[0010] A method for preparing a 1,4-DHAQ / Cu@GEL-PCL nanofiber membrane comprises the following steps: (1) Dissolving gelatin (GEL) and polycaprolactone (PCL) in an organic solvent to obtain a base solution; (2) 1,4-dihydroxyanthraquinone (1,4-DHAQ) and copper nitrate hexahydrate (Cu(NO3)2•6H2O) were added to the base liquid, and 1,4-DHAQ / Cu@GEL-PCL nanofibers were obtained by electrospinning.

[0011] In order to balance the mechanical properties and hydrophilic properties of the nanofibers, when the mass ratio of GEL and PCL is 4:1-1:4, such as 4:1, 4:2, 4:3, 4:4, 3:4, 2:4, and 1:4, the prepared electrospun nanofibers have good mechanical properties while being more conducive to the infiltration of aqueous solution on the fibers, making it easier to detect in aqueous solution.

[0012] The organic solvent is at least one of formic acid, acetic acid and chloroform; in order to make the fiber thinner and more uniform and obtain a larger specific surface area, the organic solvent is a mixture of formic acid and acetic acid; preferably, the volume ratio of formic acid to acetic acid is 1:3-3:1, such as 1:3, 1:1, 3:1.

[0013] The solubility of 1,4-DHAQ in the matrix solution under the optimal solvent conditions is limited, because the nanofiber membrane is made of Cu 2+ Based on the fluorescence change caused by the substitution reaction between 1,4-DHAQ derivatives and chromium ions, in order to improve the detection sensitivity and detection limit of the fiber membrane, a saturated solution of 1,4-DHAQ is generally selected. 2+ 1,4-DHAQ derivatives and Cr 3+ The reaction is a reversible reaction, so Cu 2+ The ratio of 1,4-DHAQ to Cu 2+ The molar ratio is 1:2.

[0014] The parameters of electrospinning will affect the morphology of the nanofiber membrane. The main influencing factors include voltage and the concentration of the substrate liquid. Preferably, the voltage is 15kV-25 kV, and independent and non-adhesive nanofiber membranes can be prepared. Preferably, the mass fraction of the substrate liquid is not less than 28%; more preferably, it is 28%-37%; more preferably, it is 31%-37%; and most preferably, it is 34%. The electrospinning time mainly affects the thickness of the nanofiber membrane. The receiver distance in the range of 10cm-20 cm has almost no effect on the fiber morphology. The feed rate range is generally 0.6-2.0 mL / h, preferably 0.8-1.2 mL / h.

[0015] A 1,4-DHAQ / Cu@GEL-PCL nanofiber membrane obtained by the above preparation method.

[0016] The above nanofibers can be used to prepare solid-state fluorescent sensors for detecting Cr in water. 3+ .

[0017] The present invention also provides a method for detecting Cr in water by using the above-mentioned nanofiber membrane or solid-state fluorescent sensor. 3+ The method comprises the following steps: S1. contacting the above-mentioned 1,4-DHAQ / Cu@GEL-PCL nanofiber membrane or solid-state fluorescent sensor with the water body to be tested; S2. Compare the fluorescence intensity of the nanofiber membrane or solid-state fluorescence sensor in step S1 with that of the nanofiber membrane or solid-state fluorescence sensor that is not in contact with the water body. An increase in the fluorescence intensity indicates that the water body contains Cr. 3+ .

[0018] The contact time with water can be determined according to the Cr content in water. 3+ The concentration is adjusted. When the Cr 3+ When the concentration is low, the contact time can be extended to reach Cr 3+ Full contact with 1,4-DHAQ. Generally, the time is not less than 5 minutes. However, due to Cu 2+ 1,4-DHAQ derivatives and Cr 3+ The reaction is a reversible reaction. Therefore, too high a contact time will lead to an increase in fluorescence intensity. 3+ Concentration (10 -4 M) the contact time exceeds 7 minutes. 3+ When the ion content is very high, such as above 10 −4 M, the contact time can be reduced; however, too short a contact time, such as less than 1 min, is likely to cause greater errors, so you can choose to dilute the sample to be tested.

[0019] The excitation wavelength of fluorescence intensity detection is 400 nm, and the detection range is 500 nm to 515 nm. 3+ A linear quantitative relationship can be established between molar concentration and fluorescence intensity, which can be used to determine the concentration of Cr in water. 3+ Concentration determination; especially the strong fluorescence emission peak around 506 nm, which can be used for more sensitive quantification.

[0020] In some embodiments, in order to detect Cr in water 3+ The quantitative detection includes the following steps: s1. The above 1,4-DHAQ / Cu@GEL-PCL nanofiber membrane or solid-state fluorescent sensor was respectively mixed with a series of concentrations of Cr 3+ The solution comes into contact with the water to be tested; s2, detecting the fluorescence intensity of the nanofiber membrane or solid-state fluorescence sensor in step s1, and establishing a series of concentrations Cr 3+ Cr in solution 3+ Functional relationship between molar concentration and fluorescence intensity; s3. Calculate Cr by the fluorescence intensity of the water to be tested 3+ concentration.

[0021] The mechanism of the present invention is as follows: The 1,4-DHAQ / Cu@GEL-PCL nanofiber fluorescence sensor provided by the present invention is doped with Cu 2+ 1,4-DHAQ derivatives can be used for qualitative and quantitative detection of Cr in aqueous solutions 3+ ions. Under normal temperature conditions, the unsaturated ketone structure contained in 1,4-DHAQ easily reacts with Cu 2+ Reacts to generate Cu 2+ The 1,4-DHAQ derivative has no fluorescence, but it can be further combined with Cr 3+ Reaction to generate Cr 3+ The 1,4-DHAQ derivatives showed fluorescence enhancement, and the reaction formula is as follows: ; The change of fluorescence can be measured by fluorescence spectrophotometer. The increase of fluorescence intensity indicates that the detection system contains Cr. 3+ .

[0022] The present invention has the following advantages: The nanofiber fluorescence sensor prepared by the present invention is effective in detecting Cr 3+ In the detection application of ions, it has high sensitivity and good stability; the pretreatment incubation time of the fluorescent sensor is 5 minutes, which is suitable for rapid detection and analysis of large quantities of samples to be tested; the preparation of the nanofiber membrane can be completed in one step, the preparation process is simple, and the raw materials are green, environmentally friendly, economical and easy to obtain; the nanofiber membrane provided by the present invention can maintain its original performance under room temperature and light-proof conditions for at least six months; the fluorescent sensor provided by the present invention is a solid sensor, which is simple to operate and easy to carry. The fluorescent sensor provided by the present invention has strong anti-interference during the detection process and does not require pretreatment, and can be widely used in the detection of various industrial wastewaters. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The nanofiber membrane prepared in Example 1 has a 3+ Response; Figure 2 is a SEM image of 1,4-DHAQ / Cu@GEL-PCL nanofibers prepared in Example 2; Figure 3is the distribution diagram of nanofiber diameter in Gaussian fitting Example 2; Figure 4 is the fluorescence intensity of the sensor at different incubation times; Figure 5 is the fluorescence intensity of the solid-state fluorescence sensor after being impregnated with different metal cations; Figure 6 Different concentrations of Cr 3+ Fluorescence intensity of the solid-state fluorescence sensor after treatment; Figure 7 Solid-state fluorescence sensor for Cr 3+ Linear fitting plot of the concentration detection range; Figure 8 These are wastewater samples from different processes in the leather industry. DETAILED DESCRIPTION

[0024] The present invention is further described below in conjunction with the examples and drawings, but the present invention is not limited by the following examples. Unless otherwise specified, the reagents in the examples are all commercially available products of analytical grade.

[0025] Example 1 Preparation of 1,4-DHAQ / Cu@GEL-PCL Nanofibers (1) GEL and PCL with a mass ratio of 4:3 were dissolved in a formic acid / acetic acid mixed solvent with a volume ratio of 3:1 to obtain base solutions with mass fractions of 25.08%, 28.08%, 31.09%, 33.96%, and 36.94%; (2) adding 1,4-DHAQ to a mass fraction of 0.1% and Cu(NO3)2•6H2O to a mass fraction of 0.2% to the above-mentioned base solution, and dissolving them by ultrasonication to obtain a spinning solution; (3) The spinning solution was loaded into the syringe and the electrospinning parameters were set as follows: voltage 20 kV, injection rate 1.0 mL / h, receiver distance 15 cm, and electrospinning for 4 h to obtain 1,4-DHAQ / Cu@GEL-PCL nanofiber membrane.

[0026] From the SEM images of each nanofiber membrane, it can be seen that: when the mass fraction is lower than 28%, only a very small number of continuous nanofibers can be formed in the electrospinning product, and there are a large number of beads and droplets interspersed between the nanofibers. The diameter of the nanofibers is uneven, and the fibers are adhered and agglomerated; with the increase of the mass fraction, the diameter of the nanofibers increases, and the adhesion and agglomeration are greatly reduced. When the mass fraction is 34%, it can be observed that a large number of independent, smooth, and straight nanofibers are formed in the state of fresh preparation and spinning, and a nanofiber membrane with good morphology can be prepared; when the mass fraction is greater than 34%, a large number of nanofibers can be clearly observed in the electrospinning product, and the diameter of the nanofibers also increases, but the formed nanofibers are bent and folded, and the diameter distribution begins to become uneven.

[0027] According to the above method, a 1,4-DHAQ@GEL-PCL nanofiber membrane with a base liquid content of 33.96% was prepared. The above 1,4-DHAQ / Cu@GEL-PCL was immersed in a 1×10 -4 M's Cr 3+ The solution was incubated for 3 min and the un-immersed Cr 3+ The 1,4-DHAQ / Cu@GEL-PCL solution and the 1,4-DHAQ@GEL-PCL nanofiber membrane were placed on the sample stage of the gel imaging instrument and the fluorescence image was observed under 312nm ultraviolet light. Figure 1 As shown in the figure: After adding 1,4-DHAQ to the electrospun membrane (a, b, c), its fluorescence intensity is significantly enhanced. Among them, the electrospun nanofiber membrane (a) prepared by adding only 1,4-DHAQ has the highest fluorescence intensity. However, the fluorescence intensity of 1,4-DHAQ / Cu@GEL-PCL (b) prepared by adding 1,4-DHAQ and Cu(NO3)2•6H2O is significantly reduced. This is because Cu 2+ Binding to 1,4-DHAQ changes the chemical structure of the fluorophore, resulting in fluorescence quenching. The fluorescence intensity of 1,4-DHAQ / Cu@GEL-PCL decreases when immersed in Cr 3+ The solution (c) increases, which is because Cu 2+ and Cr 3+ The above results show that 1,4-DHAQ / Cu@GEL-PCL has a fluorescence enhancement effect on Cr 3+ It has potential in the detection of ions.

[0028] Example 2 1,4-DHAQ / Cu@GEL-PCL nanofibers and detection of Cr 3+ Preparation of solid-state fluorescence sensor (1) GEL and PCL with a mass ratio of 4:3 were dissolved in a mixed solvent of formic acid / acetic acid with a volume ratio of 3:1 to obtain a base solution with a mass fraction of 33.96%; (2) adding 1,4-DHAQ to a mass fraction of 0.1% and Cu(NO3)2•6H2O to a mass fraction of 0.2% to the above-mentioned base solution, and dissolving them by ultrasonication to obtain a spinning solution; (3) The spinning solution was loaded into the syringe and the electrospinning parameters were set as follows: voltage 20 kV, injection rate 1.0 mL / h, receiver distance 15 cm, electrospinning for 4 hours to obtain 1,4-DHAQ / Cu@GEL-PCL nanofiber membrane with a thickness of 0.13 mm. Its SEM was as follows: Figure 2 shown.

[0029] Nano Measurer 1.2 was used to perform a statistical evaluation of the diameter of the nanofibers. Fifty nanofibers were randomly selected as samples for measuring the diameter. The Gaussian fitting results showed that the diameter of the nanofibers was 303.92 ± 11.57 nm ( Figure 3 ).

[0030] The nanofiber membrane was cut into 1 cm × 4 cm strips to obtain a simple detection method for Cr 3+ Solid-state fluorescence sensor.

[0031] Example 3 Solid-state fluorescence sensor for Cr 3+ Detection Each nanofiber prepared in Example 2 was cut into 1 cm × 4 cm strips to obtain a simple detection method for Cr 3+ Solid-state fluorescence sensor.

[0032] 1. Effect of incubation time on detection The prepared detection Cr 3+ The solid-state fluorescent sensor was immersed in 7 mL of 1×10 -4 M's Cr 3+ In the ionic solution, set the incubation time to 1, 2, 3, 4, 5, 6, and 7 minutes (3 parallel samples). After the incubation, take it out and dry it at room temperature. Place the nanofiber fluorescence sensor on the sample holder of the fluorescence spectrophotometer instrument, fix the detection distance of the sample holder, and detect the fluorescence intensity in the wavelength range of 450nm to 550nm at an excitation wave length of 400nm and record the results.

[0033] The fluorescence intensity of the sensor under different pretreatment incubation times is shown in Figure 2. Figure 4 Shown: Immersed in Cr-containing 3+ After the solution was added, the fluorescence intensity of the fluorescent sensor decreased with the passage of time and tended to be stable after 5 minutes. Therefore, 5 minutes was selected as the optimal pretreatment incubation time for the nanofiber fluorescent sensor.

[0034] 2. Selectivity of solid-state fluorescence sensors The solid-state fluorescent sensors were immersed in water with a concentration of 10 −4 Common metal cation nitrate solutions (Mg 2+ 、Al 3+ , K + 、Ni 2+ 、Na + 、Cd 2+ , Hg 2+ 、Co 2+ , Fe 3+ , Fe 2+ ) and all the above metal cations and Cr 3+ The mixed solution was incubated for 5 minutes. After the incubation, it was taken out and dried at room temperature. The nanofiber fluorescence sensor test strip was placed on the sample holder of the fluorescence spectrophotometer instrument, the detection distance of the sample holder was fixed, and the fluorescence intensity in the wavelength range of 450nm to 550nm was detected at an excitation wave length of 400nm and the results were recorded.

[0035] The results are as follows Figure 5 As shown in the figure, the solid-state fluorescent sensor prepared by 1,4-DHAQ / Cu@GEL-PCL nanofibers is effective for removing Cr 3+ Other ions hardly react, even Cr 3+ Cr can also be detected in the presence of high concentrations of other metal ions 3+ This demonstrates that the fluorescence sensor is sensitive to Cr 3+ It has good selectivity and can be used to selectively detect Cr in sample solutions. 3+ .

[0036] 3. Linear relationship range The prepared detection Cr 3+ Solid-state fluorescence sensors were immersed in 7 mL of Cr 3+ Ionic solution (2.7×10 -6 -4.3×10 -6 M) and incubated for 5 min (3 parallel samples). After the incubation, take out and dry at room temperature, place the nanofiber fluorescence sensor on the sample holder of the fluorescence spectrophotometer instrument, fix the detection distance of the sample holder, detect the fluorescence intensity in the wavelength range of 450 nm to 550 nm under the excitation wave length of 400 nm, and record the fluorescence intensity result at 506 nm.

[0037] Different concentrations of Cr 3+ The fluorescence intensity of the solid-state fluorescence sensor after treatment is as follows Figure 6 As shown, the solid-state fluorescence sensor is 3+ The linear fitting diagram of the concentration detection range is shown in Figure 7 As shown. It can be seen that when Cr 3+ The concentration is 2.7×10-6 -4.3×10 -6 M, the fluorescence intensity at 506 nm is similar to that of Cr 3+ The concentration showed a good linear relationship, and the corresponding mathematical model was: I = 54.25 [Cr 3+ ]+ 425.86, indicating that the sensor can achieve Cr 3+ Quantitative detection of ions.

[0038] 4. Sensor Storage Period The detection Cr prepared in Example 2 3+ The solid-state fluorescent sensor was stored at room temperature and away from light for six months. After being taken out, five samples containing Cr were randomly tested according to the method of Example 3. 3+ Solution samples of unknown concentration were tested by ICP-MS for comparison and verification.

[0039] Table 1 Comparison of the nanofiber fluorescence sensor and ICP-MS test results after six months of storage (×10 -6 M) The comparison and verification of the solid-state fluorescence sensor detection results and the ICP-MS detection results are shown in Table 1. It can be seen that the solid-state fluorescence sensor prepared by 1,4-DHAQ / Cu@GEL-PCL nanofiber membrane stored for six months is still reliable and does not affect the detection results.

[0040] Application example: Detection of leather wastewater using fluorescence sensor Four different types of Cr-containing 3+ Wastewater, including chrome tanning wastewater, post-tanning cleaning wastewater (cleaning wastewater), wet blue leather squeezing water (squeezing water) and retanning wastewater ( Figure 8 All water samples were filtered through a 4.5 µm filter and diluted at the same interval. Cr was measured using the detection method and solid-state fluorescence sensor in Example 5. 3+ The concentration of ions.

[0041] At the same time, the samples were analyzed using ICP-MS to verify the accuracy of the results: After centrifugation and filtration, the water samples were digested using a microwave digester to remove organic matter. After cooling to room temperature, deionized water was added to reach a constant volume. ICP-MS was then used to measure the Cr³⁺ ion concentration in the water samples after digestion and further dilution.

[0042] Table 2 Comparison of nanofiber fluorescence sensor and ICP-MS test results (g / L) 1,4-DHAQ / Cu 2+The solid-state fluorescence sensor test results prepared by @GEL-PCL nanofiber membrane were compared with the ICP-MS test results as shown in Table 2. The test results of the fluorescence sensor are similar to those of ICP-MS, with a small error range. This indicates that 1,4-DHAQ / Cu 2+ @GEL-PCL nanofiber membrane can be used for Cr in actual wastewater solution 3+ The ions can be detected, and the pretreatment method is fast and simple, without the need for digestion of organic matter.

[0043] The above is only an embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application should be included in the scope of the claims of the present application.

Claims

1. A method for preparing 1,4-DHAQ / Cu@GEL-PCL nanofiber membrane, It is characterized in that The following steps are involved: (1) dissolving gelatin and polycaprolactone in an organic solvent to obtain a base solution; (2) 1,4-dihydroxyanthraquinone and copper nitrate hexahydrate were added to the base liquid, and 1,4-DHAQ / Cu@GEL-PCL nanofibers were obtained by electrospinning.

2. The preparation method according to claim 1, It is characterized in that The mass ratio of gelatin to polycaprolactone is 4:1-1:4; The organic solvent is at least one of formic acid, acetic acid and chloroform; The molar ratio of 1,4-dihydroxyanthraquinone to copper nitrate hexahydrate is 1:2; 1,4-Dihydroxyanthraquinone is a saturated solution in the base fluid; The voltage of electrospinning is 15kV-25 kV; The mass fraction of the base liquid is not less than 28%; The receiver distance for electrospinning is 10cm-20cm; The feed rate for electrospinning was 0.6-2.0 mL / h.

3. The preparation method according to claim 1, It is characterized in that The mass ratio of gelatin to polycaprolactone is 4:1, 4:2, 4:3, 4:4, 3:4, 2:4, 1:4; the organic solvent is a mixture of formic acid and acetic acid in a volume ratio of 1:3-3:1; the mass percentage of the base liquid is 28%-37%; or 31%-37%. The feed rate of electrospinning is 0.8-1.2 mL / h.

4. The preparation method according to claim 1, It is characterized in that The volume ratios of formic acid and acetic acid are 1:3, 1:1, and 3:1; the mass percentage of the base liquid is 34%.

5. A 1,4-DHAQ / Cu@GEL-PCL nanofiber membrane obtained by the preparation method according to any one of claims 1 to 4.

6. Use of the nanofiber membrane as claimed in claim 5 in preparing a solid-state fluorescent sensor, It is characterized in that Solid-state fluorescence sensor for detecting Cr in water 3+ .

7. A method for detecting Cr in water using the nanofiber membrane as claimed in claim 5 or the solid-state fluorescent sensor as claimed in claim 6 3+ method, It is characterized in that The following steps are involved: S1. contacting the above-mentioned 1,4-DHAQ / Cu@GEL-PCL nanofiber membrane or solid-state fluorescent sensor with the water body to be tested; S2. Compare the fluorescence intensity of the nanofiber membrane or solid-state fluorescence sensor in step S1 with that of the nanofiber membrane or solid-state fluorescence sensor that is not in contact with the water body. An increase in the fluorescence intensity indicates that the water body contains Cr. 3+ .

8. A method for quantitatively detecting Cr in water using the nanofiber membrane as claimed in claim 5 or the solid-state fluorescent sensor as claimed in claim 6 3+ method, It is characterized in that The following steps are involved: s1. The above 1,4-DHAQ / Cu@GEL-PCL nanofiber membrane or solid-state fluorescent sensor was respectively mixed with a series of concentrations of Cr 3+ The solution comes into contact with the water to be tested; s2, detecting the fluorescence intensity of the nanofiber membrane or solid-state fluorescence sensor in step s1, and establishing a series of concentrations Cr 3+ Cr in solution 3+ Functional relationship between molar concentration and fluorescence intensity; s3. Calculate Cr by the fluorescence intensity of the water to be tested 3+ concentration.

9. The method according to claim 7 or 8, It is characterized in that The contact time with the water to be tested is 1-7 min; the excitation wavelength of fluorescence intensity detection is 400 nm, and the detection wavelength is 500nm to 515 nm.

10. The method according to claim 7 or 8, It is characterized in that The contact time with the water to be tested is 5-7 min; the detection wavelength of fluorescence intensity detection is 506nm.

Citation Information

Patent Citations

  • Method for preparing gelatin / polycaprolactone composite nanometer fiber membrane through electrostatic spinning

    CN102242463A

  • Porous membrane composed of cellulose doped with 1,4-dihydroxy anthraquinone and bivalent copper ion and preparation method and application thereof

    CN103084073A

  • CNTs-modified 1,4-dioxyanthraquinone doped cellulose-combined porous membrane and preparation method and application thereof

    CN106568751A

  • Gelatin / polyester fiber dressing and preparation method thereof

    CN115645592A

  • Cadmium ion detection membrane, preparation method thereof and application of cadmium ion detection membrane in cadmium detection device

    CN115897058A